Cualidades naturales y culturales del distrito de florida Pomacochas región Amazonas, para diversificar la oferta turística regional. - Tasilla Vásquez, Lenifet (2018)
The present report of Investigation is referred to the Natural and Cultural Qualities of the District of Florida Pomacochas Amazonas Region, to Diversify the Regional Tourist Offer, that had like interest to determine the natural and cultural qualities of the district of Florida Pomacochas to diversify the current regional tourist offer . It has been proven that the Pomacochas District of Florida possesses natural qualities expressed in natural resources, flora and fauna; also in cultural qualities expressed in its patronal feast, the agriculture and the cattle ranch, also the folklore manifested in stories, myths, legends, customs and traditions, and the gastronomy. Therefore, it has exceptional qualities for the development of tourism in the district, being able to become a tourist product of great importance to diversify the regional tourist offer where tourists can perform multiple activities such as flora and fauna observation, trekking, walk by boat, participation in narrative folklore, tasting of dairy products, among others. On the other hand, the method used to prepare this report was: the Analytical-Synthetic method. Handling research techniques such as: survey, interview and mainly observation. It was also necessary to review the bibliography and the signing, allowing the gathering of complementary information that makes up the theoretical body of the present investigation.